2021
DOI: 10.1186/s12959-021-00275-w
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central venous catheter in upper extremities leads to an increase in D-dimer and deep vein thrombosis in lower extremities

Abstract: Background The purpose of this study is to elucidate the association between peripherally inserted central venous catheter (PICC) in upper extremities and lower extremity deep venous thrombosis (LEDVT) by observing the changes in D-dimer. Methods This was a retrospective cohort study with 3452 patients (104 inserted with PICCs and 3348 without PICC) enrolled at the neurology department from April 1, 2017 to April 1, 2020. The patients underwent col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…It is suitable for intravenous treatment of home-care patients, thus becoming more popular with medical staff and patients [ 28 , 29 ]. But recent studies revealed that PICC markedly increased the risks of venous thrombosis [ 30 , 31 ]. The causes of PICC-related venous thrombosis may be as follows: (1) the diameter of the PICC affects the central flow in the lumen, thereby increasing the risk of turbulent flow and venous thrombosis; (2) the stiffness of the PICC and the direct venous injury and inflammation caused by the insertion, resulting in thrombosis; (3) the introduction of PICC prompts the human body to form a surrounding biofilm to isolate it, coupled with low flow and venous blood stasis, which is conducive to the thrombosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is suitable for intravenous treatment of home-care patients, thus becoming more popular with medical staff and patients [ 28 , 29 ]. But recent studies revealed that PICC markedly increased the risks of venous thrombosis [ 30 , 31 ]. The causes of PICC-related venous thrombosis may be as follows: (1) the diameter of the PICC affects the central flow in the lumen, thereby increasing the risk of turbulent flow and venous thrombosis; (2) the stiffness of the PICC and the direct venous injury and inflammation caused by the insertion, resulting in thrombosis; (3) the introduction of PICC prompts the human body to form a surrounding biofilm to isolate it, coupled with low flow and venous blood stasis, which is conducive to the thrombosis [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Asymptomatic PICC‐associated VT mainly occurred in superficial veins (Chen et al, 2021 ). Concurrently, PICC‐associated VT is unique, with most types being attached to wall thrombosis (Liu et al., 2021 ). This may be one of the important reasons for the lower negative predictive value of the D‐dimer level for diagnosing PICC‐associated VT in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of patients who undergo PICC placement in China are cancer chemotherapy patients (Liu et al, 2018 ). Moreover, PICC‐associated upper extremity vein thrombosis (UEVT) is different from the usual vein thrombus, as the former presents primarily as a mural thrombus (Liu et al., 2021 ; Winters et al., 2015 ). The different study population and the different types of VT may affect D‐dimer levels, and the question of whether they are also sensitive to rule out PICC‐associated UEVT remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“… 13 , 14 Currently, D-dimer assessment is a tool with practical value in the diagnosis of DVT and PE. 12 , 14 , 15 In practice, however, for the diagnosis of venous thromboembolism (VTE), D-dimer has a high sensitivity but a low specificity. This is because increased D-dimer levels are non-specific and could be affected by tumors, surgery, and trauma.…”
Section: Introductionmentioning
confidence: 99%
“…12 D-dimer levels that are elevated usually indicate a boost in the coagulation and fibrinolysis systems, and can be utilized as a sensitive diagnostic of hypercoagulability. 13,14 Currently, D-dimer assessment is a tool with practical value in the diagnosis of DVT and PE. 12,14,15 In practice, however, for the diagnosis of venous thromboembolism (VTE), D-dimer has a high sensitivity but a low specificity.…”
Section: Introductionmentioning
confidence: 99%